'On me bed, son': The (Re)presentation of (emphasised) femininity in English 'tabloid' newspaper coverage of Euro 2016. (November 2019) - Domeneghetti, Roger
This study explores the gendered narratives constructed in the coverage of the 2016 Union of European Football Associations (UEFA) European Championship football tournament in selected English newspapers. Using qualitative textual analysis, the study tests the efficacy of three established classifications and draws them together with a new, fourth classification thereby creating a typology of the (re)presentations of emphasised femininity. The analysis suggests that despite the increasing prevalence of female sports journalists and the increasing coverage of female athletes in a variety of sports, including football, the reporting of men's football in the English popular press continues to cast women in subordinate and sexualised roles. Furthermore, women who challenge these roles, particularly those who establish their own voice within the event's discursive space, are criticised.